Pengaruh Bauran Pemasaran Islam terhadap Keputusan Berinvestasi di Reksa Dana Syariah dengan Religiositas sebagai Variabel Moderasi - Maulana, Nurul Iman; Wulandari, Fitri (Jurnal Manajemen Bisnis dan Keuangan, 2024)
The objective of this research is to analyze the influence of the Islamic marketing mix, consisting of halal products, pricing, place, and Islamic promotion, on the decision to invest in Islamic mutual funds, with religiosity as a moderating variable. The research method used is quantitative, with a sample of 100 Islamic mutual fund investors. Data were collected through questionnaires and analyzed using multiple linear regression and moderated regression analysis. The results show that the variables of halal products, pricing, and place have a significant influence on the decision to invest in Islamic mutual funds, while Islamic promotion is not significant. The moderation analysis shows that religiosity strengthens the relationship between the Islamic marketing mix and investment decisions. The novelty of this research lies in revealing the moderating role of religiosity that enhances the influence of halal products, pricing, place, and Islamic promotion on investment decisions. The conclusion of this study is that effective marketing strategies that consider Sharia principles and the religiosity level of investors can increase investment decisions in Islamic mutual funds. The findings provide recommendations for Islamic mutual fund managers to focus on the halalness of products, competitive pricing, and ease of access for investors.